2015
DOI: 10.2147/dmso.s78008
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of sulfonylureas from patients with type 2 diabetes receiving long-term sulfonylurea and insulin combination therapy results in deterioration of glycemic control: a randomized controlled trial

Abstract: BackgroundThe benefit of sulfonylureas (SUs) to patients with type 2 diabetes mellitus receiving long-term insulin treatment is unclear. This study evaluated glycemic control and beta-cell function after SU withdrawal in these patients.MethodsIn this 8-week randomized controlled study, patients with type 2 diabetes who had been treated with insulin for at least 3 years plus moderate to high doses of SUs were randomly assigned to withdrawal (n=16) or continuation (n=16) of SUs. Clinical characteristics, glycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…A better model for evaluation of beta-cell function to correct for the confounding effects of glucotoxicity, such as inducing normoglycemia by adding insulin and subsequently reassessing beta-cell function, could be performed. However, a randomized controlled study conducted by our group (Srivanichakorn et al), in T2DM patients who achieved optimal glycemic control during long-term treatment with combined SU and insulin, showed that withdrawal of SU resulted in worsening of glycemic status 29. The findings from Srivanichakorn et al and the present study confirm that SU still plays a significant role in glycemic control in both hyperglycemic and optimal glycemic states.…”
Section: Discussionsupporting
confidence: 73%
“…A better model for evaluation of beta-cell function to correct for the confounding effects of glucotoxicity, such as inducing normoglycemia by adding insulin and subsequently reassessing beta-cell function, could be performed. However, a randomized controlled study conducted by our group (Srivanichakorn et al), in T2DM patients who achieved optimal glycemic control during long-term treatment with combined SU and insulin, showed that withdrawal of SU resulted in worsening of glycemic status 29. The findings from Srivanichakorn et al and the present study confirm that SU still plays a significant role in glycemic control in both hyperglycemic and optimal glycemic states.…”
Section: Discussionsupporting
confidence: 73%
“…15 Abrupt discontinuation of insulin or secretagogues without monitoring could inadvertently result in hyperglycemia. 16,17 We also felt professional CGM was beneficial for individualizing monitoring plans. Instead of depending on subjective feedback, clinical results were used to guide recommendations for longterm CGM use.…”
Section: Discussionmentioning
confidence: 99%
“…15 Deterioration of glycemic control is reported in multiple studies when sulfonylureas are withdrawn from therapy due to impacted insulin secretion. [16][17][18] As such, the multiplier group may have been disproportionately impacted by this factor due to the slightly greater baseline use of sulfonylureas. Accurate medication reconciliation and critical evaluation of anti-hyperglycemic medications prior to admission, including sulfonylureas, and appropriate adjustment of insulin in response would be beneficial to improve inpatient glycemic control.…”
Section: Discussionmentioning
confidence: 99%